Negativity bias and political preferences: A response to commentators. Issue 3 (27th June 2014) - Hibbing, John R.; Smith, Kevin B.; Alford, John R.
Abstract A broad, multidisciplinary empirical literature reports that individual-level differences in psychology and biology map onto variation in political orientation. In our target article we argued that negativity bias can explain a surprisingly large share of these findings. The commentators generally support the negativity bias hypothesis but suggest theoretical and empirical revisions and refinements. In this response, we organize these proposals, suggestions, and criticisms into four thematic categories and assess their potential for furthering theories and empirical investigations of the bases for individual-variation in political ideology.